A Novel Long Non‐Coding RNA lnc030 Maintains Breast Cancer Stem Cell Stemness by Stabilizing SQLE mRNA and Increasing Cholesterol Synthesis. Issue 2 (30th November 2020) - Qin, Yilu; Hou, Yixuan; Liu, Shuiqing; Zhu, Pengpeng; Wan, Xueying; Zhao, Maojia; Peng, Meixi; Zeng, Huan; Li, Qiao; Jin, Ting; Cui, Xiaojiang; Liu, Manran
Abstract: Cancer stem cells (CSCs) are considered the roots of cancer metastasis and recurrence (CSCs), due in part to their self‐renewal and therapy resistance properties. However, the underlying mechanisms for the regulation of CSC stemness are poorly understood. Recently, increasing evidence shows that long non‐coding RNAs (lncRNAs) are critical regulators for cancer cell function in various malignancies including breast cancer, but how lncRNAs regulate the function of breast cancer stem cells (BCSCs) remains to be determined. Herein, using lncRNA/mRNA microarray assays, a novel lncRNA (named lnc030) is identified, which is highly expressed in BCSCs in vitro and in vivo, as a pivotal regulator in maintaining BCSC stemness and promoting tumorigenesis. Mechanistically, lnc030 cooperates with poly(rC) binding protein 2(PCBP2) to stabilize squalene epoxidase (SQLE) mRNA, resulting in an increase of cholesterol synthesis. The increased cholesterol in turn actives PI3K/Akt signaling, which governs BCSC stemness. In summary, these findings demonstrate that a new, lnc030‐based mechanism for regulating cholesterol synthesis and stemness properties of BCSCs. The lnc030‐SQLE‐cholesterol synthesis pathway may serve as an effective therapeutic target for BCSC elimination and breast cancer treatment. Abstract : Lnc030, a novel lncRNA, is highly expressed in BCSCs and acts as a pivotal regulator in maintaining BCSC stemness and tumorigenesis. Lnc030 cooperates with PCBP2 to stabilize SQLE mRNA, resulting in an increased cholesterol which actives PI3K/Akt signaling in governing BCSC stemness. The lnc030‐SQLE‐cholesterol synthesis pathway may serve as an effective therapeutic target for BCSC elimination and breast cancer treatment.